Erythropoietin Attenuates Experimental Contrast-Induced Nephrology: A Role for the Janus Kinase 2/Signal Transducer and Activator of Transcription 3 Signaling Pathway - Yang, Jia; Zhou, Jiaojiao; Wang, Xin; Ji, Ling; Wang, Siwen; Chen, Xuelian; Yang, Lichuan (Frontiers in Medicine, 2021)
The aim of the present study was to investigate the effect of erythropoietin (EPO) on contrast-induced nephrology (CIN) in vivo and in vitro. Male C57BL/6J mice were divided into four groups: control, CIN (iohexol 6.0 g/kg), EPO (3,000 IU/kg), and CIN+EPO. Hematoxylin and eosin (H&E) staining and biochemical index analyses were performed to evaluate renal injury. The cellular proliferation rate was detected using the Cell Counting Kit-8 (CCK-8) assay. In addition, a terminal deoxynucleotidyl transferase-mediated dUTP nick end labeling (TUNEL) assay and flow cytometric assay were used to assess the apoptosis of tissue and cells, respectively. Renal protein expression associated with apoptosis, pyroptosis, and signaling pathways was determined by Western blot (WB) assays for tissues and cells. The results showed that EPO significantly decreased serum creatinine, blood urea nitrogen, and cystatin C levels and alleviated renal histological changes in vivo. The protein levels of Janus kinase 2/signal transducer and activator of transcription 3 (JAK2/STAT3) signaling pathway components were overexpressed in the EPO treatment group. Furthermore, EPO suppressed the cell apoptosis and pyroptosis; decreased the protein levels of cleaved caspase-3, Bax, gasdermin D (GSDMD), and caspase-1; and enhanced the expression of Bcl-2. In summary, EPO could exert renoprotective effect by activating the JAK2/STAT3 signaling pathway, which may be a novel potential therapy for the treatment of CIN in the clinic.